Model Proses Bisnis dan Waktu Pelayanan Peminjaman Alat Laboratorium Perguruan Tinggi - Putra, Dede Wira Trise; Putri, Dewi Eka (International Forum of Researchers and Lecturers, 2024)
Business processes in an institution are an important measure of customer satisfaction. Universities as institutions that have laboratory work units, must have service standards to ensure they are optimal. Services that are still conventional provide problems in terms of time and accuracy. One of the first steps in building a system is designing a business process that will be a reference in building the system. And there are service times that can be used as a reference in the services provided. Based on the research that has been carried out, it was found that the recommended business process model design can speed up service both in terms of time and steps.